(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2025)
Earth’s orbits host thousands of satellites that are essential for carrying out various human activities. However, the growing exploitation of these extra-atmospheric environments risks causing their congestion. This contribution examines the phenomenon of the proliferation of space debris through a brief analysis of the sector’s regulatory framework, highlighting the centrality of sustainability concerns. Finally, by employing the constitutional law method, some concluding reflections are presented to stimulate the interest of legal scholars in the matter.